Referral pattern of pregnant women coming to Cheluvamba Hospital, Mysuru, Karnataka - Jagadeesha, Bharath; Ramakrishna, Veenashree Keragodu (International Journal Of Community Medicine And Public Health, 2019)
Background: Maternal morbidity and mortality remains a major challenge. At present pregnant women can visit any level of health care irrespective of severity of their health condition. Most of the burden of these pregnant women is on tertiary centers, hence depriving the seriously ill of the expert care. Most of the pregnancies can be managed at primary level itself. This study was therefore conducted in order to describe the referral pattern of pregnant women coming to Cheluvamba Hospital, Mysuru. Methods: It was a cross sectional study conducted during September 2018 with sample size of 100. All the pregnant women who were referred in the second week of September 2018 were included in the study without using any sampling technique and data was collected by interview using the semistructured questionnaire. Results: Mean distance travelled by study participants from their residence to Cheluvamba hospital was 42.1±29.8 kilometers. Main obstetric and logistic reason for referral was because of hypertensive disorders and non-availability of doctors respectively. Average number of ANC visits and mean gestational age upon arrival at Cheluvamba hospital was 6.71±2.3 visits and 37.4±3.6 weeks respectively. Conclusions: Most common obstetric reason for referral was hypertensive disorders. A structured referral system would help both the patient and the doctor in providing necessary obstetric care.